Pengaruh Baby Massage Terhadap Peningkatan Berat Badan Bayi Usia 0-6 Bulan Di Klinik Musytasyfah Di Tahun 2025 - Lova, Nova Rati (CV. Green Publisher Indonesia, 2025)
Growth problems are not only malnutrition, but also shortness or overnutrition WHO (2018). Children have very important values, every parent expects their child to grow and develop well. Growth is a component of the developmental process, which takes place consistently. Baby massage is a therapy that provides various benefits for babies, including in terms of growth and physical development. Objective: This study was to examine the effect of baby massage on weight gain in babies aged 0-6 months. Methods: This study used quasy experimentation with a pre-test and post-test design. Using the Normality Test shows normal distributed data p > 0.05. Then the Independent Test was obtained with a Sig. value of 0.000<0.05. . The total sample of 32 babies, namely the intervention group, was given treatment routinely every 2 days for 10 days. and the control group was not given such treatment. Results: In the intervention group, the mean pre-test, which was 5150grams, and the mean post-test, which was 5806grams, there was an increase of 656grams. The mean pre-test control group was 4837gram and the mean post-test was 4811grams, there was an increase of 44 grams. Conclusion: There is an effect of Baby Massage on weight gain in babies aged 0-6 months.